Services sectors' concentration: The European Union, Greece, and the New Economic Geography - Astrid Krenz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
The aim of this article is to investigate services sectors' concentration in the European Union based on employment data and to disentangle the sector-specific developments and influential factors over time. We find that only the financial intermediation, retail trade and water transport sectors are subject to an increasing level of concentration over time. Moreover, we can detect a strong specialization tendency in the sectors of tourism and public administration for the Greek economy. Implementing a two-way fixed effects model, we find that knowledge spillovers as well as externalities arising from technological similarities appear to be highly significant in explaining services' concentration patterns for the European Union. Technological differences as a reason for services' concentration only appear to have been important in the period prior to the Single European Market Enactment. Further evidence is found for the relevance of factor intensity in explaining concentration of non-market services.
Keywords: F14; L80; R12; 330; concentration; services; European Union; knowledge spillovers; technological similarities